The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/13032917.2019.1708423
|View full text |Cite
|
Sign up to set email alerts
|

Talent Management in the Tourism and Hospitality Industry: Evidence from Iran

Abstract: This study investigates the notion of talent in the tourism and hospitality (TH) industry, proposing a comprehensive talent management (TM) model that is specific to this industry. This study primarily explores the notion of talent, TM, and the importance of these in the industry. A mixed method approach (qualitative and quantitative) was used to fulfill the research objectives. Qualitative content analysis was used to address interview responses from a panel of experts and a survey method was applied to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(40 reference statements)
0
15
0
1
Order By: Relevance
“…In the business management literature, there is no unanimous definition of talent exists (Thunnissen et al, 2013a , p.1754; Thunnissen et al, 2013b , p.327; McDonnell et al, 2017 , p.109; Golubovskaya et al, 2019 , p.4109; Harsch and Festing, 2020 , p.45). When firms’ perceptions on the meaning and scope of talent are examined, it is observed that their considerations on this issue are shaped and varied according to their own organizational dynamics, inherently, this situation makes it difficult to develop a de facto definition (Iles et al, 2010 , p.180; Tansley, 2011 , p.266; Latukha, 2015 , p.1061; Chung and D’Annunzio-Green, 2018 , p.104; Bagheri et al, 2020 , p.88). Yet, there are some important attempts regarding to the characterization of the talent phenomenon (see Table 2 in Appendix 1 ).…”
Section: Talent Management: Existing Concepts and Debatesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the business management literature, there is no unanimous definition of talent exists (Thunnissen et al, 2013a , p.1754; Thunnissen et al, 2013b , p.327; McDonnell et al, 2017 , p.109; Golubovskaya et al, 2019 , p.4109; Harsch and Festing, 2020 , p.45). When firms’ perceptions on the meaning and scope of talent are examined, it is observed that their considerations on this issue are shaped and varied according to their own organizational dynamics, inherently, this situation makes it difficult to develop a de facto definition (Iles et al, 2010 , p.180; Tansley, 2011 , p.266; Latukha, 2015 , p.1061; Chung and D’Annunzio-Green, 2018 , p.104; Bagheri et al, 2020 , p.88). Yet, there are some important attempts regarding to the characterization of the talent phenomenon (see Table 2 in Appendix 1 ).…”
Section: Talent Management: Existing Concepts and Debatesmentioning
confidence: 99%
“…Efforts to create a general definition of talent management will be futile, because each business creates the scope and meaning of talent according to its own dynamics, and naturally their understanding and approach to talent management also differ. As a result of this fact, trying to form common expressions in an area where subjectivity is so intense can be considered as an almost impossible action (Burbach and Royle, 2010 , p.415; McDonnell et al, 2011 , p.178; Jones et al, 2012 , p.402; Pandita and Ray, 2018 , p.187; Bagheri et al, 2020 , p.88). Nevertheless, there are important attempts of academic researchers related with the definition of talent management (see Table 3 in Appendix 2 ), which can be sufficiently suited to the academic need to stimulate theory development while reflecting the interests of practitioners (Garrow and Hirsh, 2008 , p.390; Thunnissen et al, 2013a , p.1749–1750; Cappelli and Keller, 2014 , p.307; Tafti et al, 2017 , p.16).…”
Section: Talent Management: Existing Concepts and Debatesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a short-term solution, some have employed migrant labour; however, this impacts upon organisational sustainability (Marinakou and Giousmpasoglou, 2019). It has therefore been suggested that the sectors need to invest in nurturing and managing talent, which will strengthen their image as an employer of choice to overcome key challenges such as service inefficiency and labour deficits (Bagheri et al , 2020).…”
Section: Introductionmentioning
confidence: 99%